Drag-Reduction Study and its Dynamic Characteristics on Recreational Speedboat Utilizing Simplified Shark Skin Design - M.D, Ibrahim; S.N.A, Amran; Y.S, Yunos; Rahman M.R, A; M.Z, Mohtar; L.K, Wong; A, Zulkharnain (International Journal of Engineering and Technology, 2018)
Inspired by the structure of the shark skin denticles, our team has carried out a study on the attempt of improving the hydrodynamic design of marine vessels through design modification on the hull form by applying simplified imitation of shark skins. Speedboat models used in this study were designed using computer-aided design (CAD) software and computational fluid dynamic (CFD) simulations were then carried out to predict the hydrodynamic effect of the bio mimicry application on the hull form, mainly focusing on the wave profile produced by the models as well as the total drag experienced by it under two different Froude value; Frâ‰ˆ 0.39 and Frâ‰ˆ0.47. Interestingly, the design modification on the hull gave encouraging results with a reduction of 12% and 10.4% at Frâ‰ˆ 0.39 and Frâ‰ˆ0.47 respectively on the total drag coefficient. Furthermore, the modified speedboat provides better wave pattern compared to unmodified hull form. The reduction of drag force could contribute to a more efficient vessel with better cruising speed. Thus, this provide better impact to marine industry in order to help improve their vessel dynamic performances.Â